Contextualizing the Body : An Indian Experience - Kumar, Sudit Krishna,; Sarkar, Suvobrata, (Brill | Manohar Publishers & Distributors, 2021)
The new cultural history has rendered the historical epistemology of the human body a privileged site for scholarly intervention in social anthropology and other related disciplines. As a cultural metaphor, as manifestation of lived experience, as medium of existential encounter with the outer world and as a surface of social calligraphy, the human body spans varied categories of the extant strands of contemporary hermeneutic discourses. The essays in the present volume regard the human body more as a social subject than a social object. The volume accommodates variegated encounters of the biological body with the exterior world mostly from an Indian standpoint. The authors have explored the varied experiences of being embodied - the social subject's interactions with the surrounding context - as also its role as carrier of cultural, social and symbolical agents. While exploring the various contours of the 'corporeal self' the authors have captured fascinating glimpses of the 'representative' body. The present volume does not claim to represent a comprehensive account of body history. It is rather an incoherent bundle of scholarly conceptualizations of the human body discursively shaped to facilitate practices of knowledge production.